Immunomodulatory, trypanocide, and antioxidant properties of essential oil fractions of Lippia alba (Verbenaceae) - Wendy Lorena Quintero; Erika Marcela Moreno; Sandra Milena Leal Pinto; Sandra Milena Sanabria; Elena Stashenko; Liliana Torcoroma García (BMC, 2021)
Abstract Background Parasite persistence, exacerbated and sustained immune response, and continuous oxidative stress have been described to contribute to the development of the cardiac manifestations in Chronic Chagas Disease. Nevertheless, there are no efficient therapies to resolve the Trypanosoma cruzi infection and prevent the disease progression. Interestingly, trypanocide, antioxidant, and immunodulatory properties have been reported separately for some major terpenes, as citral (neral plus geranial), limonene, and caryophyllene oxide, presents in essential oils (EO) extracted from two chemotypes (Citral and Carvone) of Lippia alba. The aim of this study was to obtain L. alba essential oil fractions enriched with the aforementioned bioactive terpenes and to evaluate the impact of these therapies on trypanocide, oxidative stress, mitochondrial bioenergetics, genotoxicity, and inflammatory markers on T. cruzi-infected macrophages. Methods T. cruzi-infected J774A.1 macrophage were treated with limonene-enriched (ACT1) and citral/caryophyllene oxide-enriched (ACT2) essential oils fractions derived from Carvone and Citral-L. alba chemotypes, respectively. Results ACT1 (IC50 = 45 ± 1.7 μg/mL) and ACT2 (IC50 = 80 ± 1.9 μg/mL) exhibit similar trypanocidal effects to Benznidazole (BZN) (IC50 = 48 ± 2.5 μg/mL), against amastigotes. Synergistic antiparasitic activity was observed when ACT1 was combined with BZN (∑FIC = 0.52 ± 0.13 μg/mL) or ACT2 (∑FIC = 0.46 ± 1.7 μg/mL). ACT1 also decreased the oxidative stress, mitochondrial metabolism, and genotoxicity of the therapies. The ACT1 + ACT2 and ACT1 + BZN experimental treatments reduced the pro-inflammatory cytokines (IFN-γ, IL-2, and TNF-α) and increased the anti-inflammatory cytokines (IL-4 and IL-10). Conclusion Due to its highly trypanocidal and immunomodulatory properties, ACT1 (whether alone or in combination with BZN or ACT2) represents a promising L. alba essential oil fraction for further studies in drug development towards the Chagas disease control.